DESCRIPTIVE ANALYSIS OF CLASSROOM MANAGEMENT STRATEGIES FOR THE ENGLISH TEACHER - Mitha Huziah; Novarita Novarita (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2022)
The purpose of this study was to determine the classroom management strategies ofEnglish teachers at SMP N 32 OKU and SMP N 10 OKU. This study uses a qualitativedescription where the population were the English teachers. The number ofpopulations in this study were 11 teachers from 2 schools, the sampling was done bypurposive sampling because all samples represented all grade levels. There were 8 teachers from SMPN 32 and 3 English teachers from SMPN 10 were taken as sample. Observation and documentation are used for data collection. The instruments in thisstudy were observation and documentation. The results of the observation indicatesthat the classroom management strategy of the English teachers used 1) Get set uppreparation is when the teacher will start learning in class the teacher prepares thelesson plans. 2) Make the room attractive is the teacher prepares a classroom that isfun, neat and comfortable. 3) Set classroom rules is the teacher sets a rule in theclassroom so that students can learn responsibly. 4) the teacher always providesmotivation and solutions to students. 5) the teacher being fair, namely by creatingtogetherness and paying attention to all students. The results of the supporting documentation are the RPP for the English teacher with different materials and it canbe seen by the activities that the teacher has done. This means that the classroommanagement strategy by English teacher at SMP N 32 OKU dan SMP N 10 OKU isrunning well, optimally and in accordance with existing steps.